Revisiting Autonomy in Artificial Intelligence Through Agentic System Design - Lakshmi RahulReddy , Mareddy, (Journal of Computational Analysis and Applications (JoCAAA), 2026)
The emergence of Agentic Artificial Intelligence (AI) marks a paradigm shift from reactive andtaskspecific systems toward autonomous, goal-directed, and self-adaptive intelligence. Recent advances highlight the need for AI systems